Validation of the Revised Collett–Lester Fear of Death Scale in a French Population - Cuniah, Maeva; Bréchon, Geneviève; Bailly, Nathalie (Frontiers in Psychology, 2021)
Death and dying are processes that every human being encounters in his or her lifetime and perhaps the greatest loss an individual can suffer. In this sense, fear of death is regarded as a risk and maintaining factor of psychopathology. As such, effective and efficient measurement of this construct becomes a priority. While the Revised Collett-Lester Fear Of Death Scale (CL-FODS) is a brief, commonly used assessment, such a tool is lacking in French clinical practice. The present study aimed to adapt the revised CL-FODS in a general French sample and to determine its psychometric properties, namely its factorial structure, concurrent and convergent validity, and internal consistency. A sample of 590 participants responded to the French revised CL-FODS, as well as three instruments assessing death anxiety (DAS), neuroticism and spirituality (FACIT-Sp), to examine the internal consistency, validity and factorial structure of the scale. Both exploratory and confirmatory factor analysis confirmed a four-factor model: (1) One’s Own Death”, (2) The Death of Others, (3) The Dying of Others, and (4) One’s Own Dying. Five items did not load on these four factors, suggesting that the revised CL-FODS might require further psychometric refinement. The revised CL-FODS showed good internal consistency. The scale was found to be significantly associated with the Death Anxiety Scale. When the appropriate psychometric characteristics are taken into account, this scale can be used in clinical and research settings to assess death concerns in French society.